2005
DOI: 10.1002/hep.20802
|View full text |Cite
|
Sign up to set email alerts
|

CD154–CD40 interactions drive hepatocyte apoptosis in murine fulminant hepatitis†

Abstract: The CD154 -CD40 interaction is a critical costimulatory pathway modulating the cellular immune response. Moreover, fulminant hepatitis of various etiologies is characterized by a hepatic influx of CD154-expressing T cells and an upregulation of CD40 expression on Kupffer cells and hepatocytes, implicating this pathway in the pathogenesis of fulminant hepatitis. In this study, we used a murine model of fulminant hepatitis induced by concanavalin A (con A) and documented a significant influx of CD154-expressing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 47 publications
1
26
1
1
Order By: Relevance
“…1 and 2), it was very surprising that singular or combined neutralization of IFN-g or TNF-a had no effect on the liver pathology of infected WSX-1 2/2 mice, although this is in agreement with a previous study where administration of anti-IFN-g did not affect the outcome of T. gondii infection (15). Alternatively, WSX-1 2/2 CD4 + T cells may mediate their damaging effects on hepatocytes directly via FAS-FAS ligand or CD154-CD40 interactions and/or by the production of proteases (39)(40)(41). Experiments are under way to test these hypotheses and to elucidate the IL-27-dependent pathways controlling migration to and accumulation of effector CD4 + T cells within the liver during malaria infection.…”
Section: Discussionsupporting
confidence: 90%
“…1 and 2), it was very surprising that singular or combined neutralization of IFN-g or TNF-a had no effect on the liver pathology of infected WSX-1 2/2 mice, although this is in agreement with a previous study where administration of anti-IFN-g did not affect the outcome of T. gondii infection (15). Alternatively, WSX-1 2/2 CD4 + T cells may mediate their damaging effects on hepatocytes directly via FAS-FAS ligand or CD154-CD40 interactions and/or by the production of proteases (39)(40)(41). Experiments are under way to test these hypotheses and to elucidate the IL-27-dependent pathways controlling migration to and accumulation of effector CD4 + T cells within the liver during malaria infection.…”
Section: Discussionsupporting
confidence: 90%
“…Zhou and coworkers, 23 in a concanavalin A model, reported that the CD40L-CD40 interaction plays a major role in triggering hepatocellular apoptosis by demonstrating that hepatitis, tumor necrosis factor ␣ levels, and hepatocyte death was significantly attenuated in CD40L Ϫ/Ϫ mice.…”
Section: Discussionmentioning
confidence: 99%
“…Several human 2,4 and animal [24][25][26][27] studies using CD40 agonists report elevated levels of circulating hepatocyte enzymes ALT and AST, indicative of liver damage. To examine the severity of hepatocellular damage with monotherapy versus combination therapy, we measured plasma levels of ALT and AST in mice after vaccination ( Figure 5A,B).…”
Section: ␣Cd40-induced Hepatocellular Injury Is Reduced By Coadministmentioning
confidence: 99%